2021
DOI: 10.3390/cancers13246301
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-9 Supports the Tumor-Promoting Environment of Chronic Lymphocytic Leukemia

Abstract: Interleukin (IL)-9 is a soluble factor secreted by immune cells into the microenvironment. Originally identified as a mediator of allergic responses, IL-9 has been detected in recent years in several tumor niches. In solid tumors, it mainly promotes anti-tumor immune responses, while in hematologic malignancies, it sustains the growth and survival of neoplastic cells. IL-9 has been recently implicated in the pathogenesis of chronic lymphocytic leukemia; however, the molecular mechanisms underlying its contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 106 publications
(164 reference statements)
0
8
0
Order By: Relevance
“…We have previously reported that leukemic cells from CLL patients shape the lymphoid microenvironment to promote their survival while suppressing anti-cancer immunity through both contact-dependent and contact-independent interactions (Patrussi et al, 2021; Boncompagni et al, 2024). In particular, we showed that CLL cells enhance their surface expression of the immunosuppressive ligand PD-L-1 (Lopresti et al, 2024) and induce the upregulation of the inhibitory receptor PD-1 on CTLs (Boncompagni et al, 2024), leading to impaired CTL IS formation and CTL-mediated killing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that leukemic cells from CLL patients shape the lymphoid microenvironment to promote their survival while suppressing anti-cancer immunity through both contact-dependent and contact-independent interactions (Patrussi et al, 2021; Boncompagni et al, 2024). In particular, we showed that CLL cells enhance their surface expression of the immunosuppressive ligand PD-L-1 (Lopresti et al, 2024) and induce the upregulation of the inhibitory receptor PD-1 on CTLs (Boncompagni et al, 2024), leading to impaired CTL IS formation and CTL-mediated killing.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that CLL cells have the ability to rewire cellular components of the lymphoid niche, which is their primary TME, to enhance their homing to and persistence therein, where they are exposed to survival factors and protected from apoptosis-inducing drugs. These include stromal cells, which upregulate their production of homing chemokines (Patrussi et al, 2021), and CTLs themselves, which upregulate PD-1 expression (Boncompagni et al, 2024). Here we identified a new, additional immunosuppressive strategy whereby CLL cells disable CTLs by downregulating the expression of key components of their cytotoxic machinery.…”
Section: Discussionmentioning
confidence: 99%
“…7F, Supplementary Table 4), suggesting that the response of CLL patients to BTK inhibitors results, at least in part, from the normalization of IL-9 release by leukemic cells. Abnormal IL-9 secretion by leukemic cells of CLL patients [17,[31][32][33] and E-TCL1 mice [17] correlates with aggressive disease hallmarks, such as unmutated IGHV, low p66Shc levels [15,17], and lower overall survival [17]. The pro-tumoral activity of IL-9 involves its ability to promote homing chemokine secretion by stromal cells of lymphoid organs [15,17], thereby attracting CLL cells to the pro-survival lymphoid niche.…”
Section: Ex Vivo and In Vivo Inhibition Of Btk Enhances Il-9 Expressi...mentioning
confidence: 99%
“…Abnormal IL-9 secretion by leukemic cells of CLL patients [17,[31][32][33] and E-TCL1 mice [17] correlates with aggressive disease hallmarks, such as unmutated IGHV, low p66Shc levels [15,17], and lower overall survival [17]. The pro-tumoral activity of IL-9 involves its ability to promote homing chemokine secretion by stromal cells of lymphoid organs [15,17], thereby attracting CLL cells to the pro-survival lymphoid niche. Here we found that IL-9 secreted by CLL cells also participates in their escape from CTL-mediated killing by hampering IS formation in CTLs.…”
Section: Ex Vivo and In Vivo Inhibition Of Btk Enhances Il-9 Expressi...mentioning
confidence: 99%
See 1 more Smart Citation